Phosphodiesterase 2A and 3B variants are associated with primary aldosteronism. Issue 1 (January 2021) - Rassi-Cruz, Marcela; Maria, Andrea G; Faucz, Fabio R; London, Edra; Vilela, Leticia A P; Santana, Lucas S; Benedetti, Anna Flavia F; Goldbaum, Tatiana S; Tanno, Fabio Y; Srougi, Vitor; Chambo, Jose L; Pereira, Maria Adelaide A; et al.
Abstract: Familial primary aldosteronism (PA) is rare and mostly diagnosed in early-onset hypertension (HT). However, 'sporadic' bilateral adrenal hyperplasia (BAH) is the most frequent cause of PA and remains without genetic etiology in most cases. Our aim was to investigate new genetic defects associated with BAH and PA. We performed whole-exome sequencing (paired blood and adrenal tissue) in six patients with PA caused by BAH that underwent unilateral adrenalectomy. Additionally, we conducted functional studies in adrenal hyperplastic tissue and transfected cells to confirm the pathogenicity of the identified genetic variants. Rare germline variants in phosphodiesterase 2A ( PDE2A ) and 3B ( PDE3B ) genes were identified in three patients. The PDE2A heterozygous variant (p.Ile629Val) was identified in a patient with BAH and early-onset HT at 13 years of age. Two PDE3B heterozygous variants (p.Arg217Gln and p.Gly392Val) were identified in patients with BAH and HT diagnosed at 18 and 33 years of age, respectively. A strong PDE2A staining was found in all cases of BAH in zona glomerulosa and/or micronodules (that were also positive for CYP11B2). PKA activity in frozen tissue was significantly higher in BAH from patients harboring PDE2A and PDE3B variants. PDE2A and PDE3B variants significantly reduced protein expression in mutant transfected cells compared to WT. Interestingly, PDE2A and PDE3B variants increased SGK1 and SCNN1G/ENaCg at mRNA or protein levels. In conclusion, PDE2A and PDE3B variants were associated with PA caused by BAH. These novel genetic findings expand the spectrum of genetic etiologies of PA.